An overview of ELISA: a review and update on best laboratory practices for quantifying peptides and proteins in biological fluids - Aydin, Suleyman; Emre, Elif; Ugur, Kader; Aydin, Mustafa Ata; Sahin, Ibrahim; Cinar, Vedat; Akbulut, Taner (Sage Publications Ltd, 2025)
The enzyme-linked immunosorbent assay (ELISA) detects antigen-antibody interactions by using enzyme-labelled conjugates and enzyme substrates that generate colour changes. This review aims to provide an overview of ELISA, its various types, and its applications in detecting metabolites in biological fluids. The article discusses the history of the assay, its underlying principles and procedures, common ELISA protocols, and the most accurate and reliable techniques for measuring peptide molecules in biological fluids. Additionally, we emphasize best laboratory practices to achieve consistent, high-quality results and outline the essential materials for setting up an ELISA laboratory, drawing from our over 30 years of experience in the field.
Keywords: Biological fluids, ELISA, antibody, antigen; enzyme-linked immunosorbent assay